OTORITAS POLITIK DALAM KODIFIKASI MUSHAF PADA MASA KHULAFĀ’ AL-RĀSYIDĪN - MUHAMMAD ANSHORI (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This paper seeks to explore the history of the study of codification of manuscripts which still remains problematic. Even some Muslim thinkers doubt the authenticity of the manuscripts circulating now, or commonly referred to as Mushaf ‘Uṡmāni. In Islamic history, the Qur'an at the time of the Prophet Muhammad was not codified as it is now. At that time, the diversity of reading methods (qirā'ah) was so rich that many friends had their own manuscripts. But in the time of ‘Uṡmān, the Mushaf only had one version because the other Manuscripts were “destroyed